2017
DOI: 10.1016/j.palaeo.2017.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Biotic recovery after the end-Triassic extinction event: Evidence from marine bivalves of the Neuquén Basin, Argentina

Abstract: We analyze the Late Triassic extinction and Early Jurassic recovery of bivalve faunas within marine environments in the Atuel River area of the Neuquén Basin, Argentina. Data were collected from a hundred samples with invertebrates in a well-exposed uppermost Triassic to lower Jurassic section in the Neuquén Basin (southern Mendoza Province, Argentina) and allow a high-resolution reconstruction of the local diversity dynamics. The nearly continuous presence of marine stenohaline major taxa such as cnidarians, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
0
12
0
1
Order By: Relevance
“…Johnson (1984) Panthalassic records of bivalves from the South America have received considerable attention (e.g. Aberhan, 1994;Damborenea, 1987aDamborenea, , 1987bDamborenea et al, 2017), although temporal size data is mostly absent.…”
Section: Bivalve Size Changes Across Europe and Beyondmentioning
confidence: 99%
“…Johnson (1984) Panthalassic records of bivalves from the South America have received considerable attention (e.g. Aberhan, 1994;Damborenea, 1987aDamborenea, , 1987bDamborenea et al, 2017), although temporal size data is mostly absent.…”
Section: Bivalve Size Changes Across Europe and Beyondmentioning
confidence: 99%
“…High diversity shell beds with low dominance and highly specialised forms are reported from early Hettangian of Tibet (Hautmann et al, 2008). In the Neuquén Basin, Argentina, recovery appears slower than Tibet, because there is an interval barren of bivalves roughly equivalent to the planorbis Zone, followed by rising diversity and increased occupation of tiering until the canadensis Zone equivalent to the upper angulata Zone (Damborenea et al, 2017).…”
Section: Recoverymentioning
confidence: 99%
“…Such a simple measure is not suitable for the British record of the recovery from the end-Triassic mass extinction, because diversity in the pre-extinction interval was low due to unusual salinities that were quite different to the fully marine settings that develop in the aftermath (Hallam and El Shaarawy, 1982). A period of rising diversity followed by stabilisation may provide a better assessment of the recovery interval (Damborenea et al, 2017). An alternative four-phase model for recovery, incorporating ecological parameters, was created based on observations of the recovery following the end-Permian mass extinction (Twitchett, 2006, referred to here as the Twitchett recovery model).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the diversification of the crown clades of extant conifers, between 190 and 160 Mya in the Early to Middle Jurassic (Leslie et al, 2018), coincides well with the 165 Mya Daohugouthallus ciliiferus fossil, thus providing the earliest known evidence of the existence of epiphytic macrolichens. Notably, various other groups of organisms underwent radiations in this period, such as mammals or the avian stem lineage (Benson et al, 2014;Close et al, 2015). The Mid-Mesozoic era was a cooling and greenhouse period (Willis and Niklas, 2004) and the palaeoenvironment of the Daohugou formation has been described as humid, warm-temperate and montane (Ren and Krzeminski, 2002;Tan and Ren, 2002;Zhang et al, 2006), thus favoring the potential growth of epiphytic macrolichens, as shown by the ecology of extant macrolichen lineages in the tropics.…”
Section: The Importance Of Daohugouthallaceae For Our Understanding Of Macrolichen Evolutionmentioning
confidence: 99%